Epidemiology of Breast Cancer – Current Figures and Trends - Eisemann, N.; Waldmann, A.; Katalinic, A. (Geburtshilfe und Frauenheilkunde, 2013)
The epidemiology of breast cancer has clearly changed in the past few years. On the basis of current data from population-based cancer registries characteristic numbers for incidence, prevalence, mortality and survival after breast cancer are presented. The number of incident cases has increased to around 72 000 in 2009 (+ 23 % since 2003). It is estimated that at present 250 000 women with a prevalent breast cancer (5-year prevalence) are living in Germany. The most frequent localisation is the outer upper quadrant of the breast. Poorly differentiated or undifferentiated tumour tissue is found in every third patient. Since 2003 the age-standardised mortality has declined slightly (− 9 %) whereas the relative survival has improved from 79 to 86 %. Changes in the epidemiology of breast cancer can most probably be attributed to the introduction of early detection programmes such as mammography screening as well as to improved treatment options. To what extent mammography screening will lead to a further reduction of mortality remains to be seen.
Keywords: breast cancer; epidemiology; prevalence; incidence; prognosis; mortality